2020
DOI: 10.1136/bmjopen-2020-039640
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dietary magnesium intake and rheumatoid arthritis in US women: a cross-sectional study

Abstract: ObjectivesDiet has been shown to be associated with rheumatoid arthritis (RA), and magnesium has been shown to inhibit inflammatory responses, but research on the relationship between dietary magnesium and RA is limited and controversial. In this study, we aimed to explore the non-linear relationship between dietary magnesium intake and RA in US women.DesignCross-sectional survey.SettingNational Health and Nutrition Examination Survey (NHANES).Primary and secondary outcome measuresNon-linear relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…12 A threshold effect has been reported for dietary magnesium intake and risk of RA whereby moderate doses of magnesium (184-446 mg/day) were associated with the lowest prevalence of RA but lower or higher levels had higher prevalence. 13 Similarly, we find here variable odds of remaining in remission according to baseline magnesium levels.…”
Section: Accepted Articlesupporting
confidence: 73%
“…12 A threshold effect has been reported for dietary magnesium intake and risk of RA whereby moderate doses of magnesium (184-446 mg/day) were associated with the lowest prevalence of RA but lower or higher levels had higher prevalence. 13 Similarly, we find here variable odds of remaining in remission according to baseline magnesium levels.…”
Section: Accepted Articlesupporting
confidence: 73%
“…Arablou et al demonstrated that Mg intake was negatively associated with the inflammatory factors of RA such as Prostaglandin E2 [ 15 ]. Another large NHANES study reported a U-shaped linking between Mg intake and RA in US women [ 22 ]. A dietary intake range of 181 ~ 464 mmol/day was found to remain the lowest prevalence of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple articles have been published on this topic, all of which have consistently demonstrated a significant connection between these two entities. Therefore, addressing magnesium deficiency in patients with rheumatoid arthritis may be a useful therapeutic strategy to mitigate symptoms and improve patient outcomes [ 65 , 66 , 67 , 68 ]. Moreover, hypomagnesemia is a possible risk factor for severe infections in patients with systemic lupus erythematosus [ 69 ].…”
Section: Hypomagnesemia and The Immune Systemmentioning
confidence: 99%